Development of an aqueous based pesticide system - Gašić, Slavica M (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2012)
It is well known that emulsifiable concentrates (EC) formulation, beside good properties has the problem with high percent of solvent which is present and because of that are not environmental friendly and can cause problems to the user. The interest for developing emulsions oil in water (EW) instead emulsifiable concentrates is increasing due the toxicological problems of the solvent. Emulsion oil in water can reduce phytotoxicity, ecotoxicity and dermal toxicity, have a higher flash point than EC and are safer in transport and storage; also EW are more compatible with water based SC formulations for blends of active ingredients. Plant protection is often connecting with use some of pyretroide as active ingredients, for example Cypermethrin, alone or altogether with Chlorpyrifos. It is very old product which is formulated as EC formulation. In this study emulsion oil in water (EW) was developed with the same actives materials. The formulation was tested and the results ware shown that it is stable and could be used in plant protection.